Credit spread interdependencies of European states and banks during the financial crisis - Alter, Adrian; Schüler, Yves S. (Journal of Banking & Finance, 2012)
We investigate the interdependence of the default risk of several Eurozone countries (France, Germany, Italy, Ireland, the Netherlands, Portugal, and Spain) and their domestic banks during the period between June 2007 and May 2010, using daily credit default swaps (CDS). Bank bailout programs changed the composition of both banks’ and sovereign balance sheets and, moreover, affected the linkage between the default risk of governments and their local banks. Our main findings suggest that in the period before bank bailouts the contagion disperses from bank credit spreads into the sovereign CDS market. After bailouts, a financial sector shock affects sovereign CDS spreads more strongly in the short run. However, the impact becomes insignificant in the long term. Furthermore, government CDS spreads become an important determinant of banks’ CDS series. The interdependence of government and bank credit risk is heterogeneous across countries, but homogeneous within the same country.